(untitled) (Libya Journal of Geographical Studies, 2023)
This study aims at defining priorities of 3rd order basins in Wadi Majer Basin in terms of soil erosion and maintenance by applying geographical information system (GIS) depending on Digital Elevation Model (DEM) with resolution 30*30 m in order to determine the boundaries of Wadi Majer Basin and those of 3rd order basins, extract waterways network therein, classify their orders according to (Strahler 1957) and directly extract their basic morphometric properties such as area of basins, length and length of their circumference, no. and length of waterways therein. Mathematical formula in this respect were used in computing values of linear morphometric properties such as drain density, river frequency, basin texture, length of lamellar flow and bifurcation ratio in addition to computation of formal morphometric properties such as elongation ratio, rotation ratio, merger coefficient. Thereafter, morphometric properties analysis model was applied to 3rd order basins in Wadi Majer basin via the composite factor table in order to define priorities of 3rd order basins in Wadi Majer Basin in terms of soil erosion and maintenance. The study was subdivided into six axes, where the Axis (1) includes the theoretical framework of the study, while Axis (2) was dedicated to the general natural properties for Wadi Majer basin (Geological, climatic, soil). Axis (3) tackles the steps of defining priorities of 3rd order basins in Wadi Majer Basin in terms of soil erosion and maintenance and Axis (4) deals with analyzing the morphometric properties of 3rd order basins in Wadi Majer Basin, Axis (5) deals with defining priorities of 3rd order basins in Wadi Majer Basin in terms of soil erosion and maintenance and finally Axis (6) includes findings and recommendations. The study reached to defining priorities of 3rd order basins in Wadi Majer Basin in terms of soil erosion and maintenance where levels of priorities in terms of soil erosion and its need to maintenance ranged from low, medium and high in addition to creation of geographical database for morphometric properties of 3rd order basins in Wadi Majer Basin which can be utilized together with studies relevant to management and exploitation of Wadi basins in addition to other environmental studies.